Today's development of the benefits of outsourcing accounting services - Abdulloev Asliddin Junaydullaevich; Yo'ldoshev Shohjahon To'lqinovich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
This article analyzes the benefits of accounting outsourcing and its role in today's world economy, especially in investor activities. In Uzbekistan, which is currently developing rapidly, outsourcing, in particular, accounting services, is one of the most widely developing areas.